Kim jest oblubieniec w przypowieści o dziesięciu pannach (Mt 25,1-13)? Między tradycyjnymi i współczesnymi próbami zrozumienia - Zawadzki, Arnold (The Biblical Annals, 2019)
The main aim of the article is to compare carefully the intricated history of the exegesis of the Parable of the Ten Virgins (Mt 25:1-13) with the modern attempts to understand it, using the historical criticism. In fact, the historical criticism shows a number of problems concerning the critica textus, as well as the difficult process of edition, which influenced the understanding of the parable over the centuries. But the most important question, that resonates with the article, is the identity of the bridegroom: is he Jesus himself or the personification of the social injustice?